ANALISIS KESULITAN SISWA SEKOLAH DASAR DALAM MENENTUKAN PENGGUNAAN FPB DAN KPK PADA SOAL CERITA MATEMATIKA - Surani; Henry Aditia Rigianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research is motivated by the observation of difficulties experienced by elementary school students in solving mathematical word problems, particularly concerning the Greatest Common Factor (GCF) and the Least Common Multiple (LCM). The primary aim of this study is to understand in more depth the types of these difficulties and their contributing factors. This research employed a qualitative approach with a descriptive method. The subjects of the study were 5th-grade students at SD N Bibis. To collect data, we used several methods: diagnostic tests to observe student error patterns, semi-structured interviews to ascertain students' perspectives and the root causes of their difficulties, and document analysis of student work. The research findings indicate that students indeed experience difficulties in several important areas. These include: (1) a lack of understanding of the information present in word problems, (2) difficulty converting word problems into appropriate mathematical forms or sentences, (3) confusion in determining whether a problem should be solved with GCF or LCM, and (4) errors in performing basic mathematical calculations. Several factors that contribute to these difficulties are: insufficient understanding of the basic concepts of GCF and LCM, limited experience of students in working on various types of word problems, obstacles in understanding the language or terms used in the problems, and a lack of enthusiasm and interest in the subject matter. This research concludes that to overcome these difficulties, it is crucial to emphasize a more in-depth conceptual understanding, provide ample varied and contextual word problem practice, utilize engaging and interactive learning media, and regularly train students' problem-solving skills.